Design of high efficiency and wideband dual-functional metasurface for polarization conversion and asymmetric transmission - Nguyen Thi Quynh, Hoa; Nguyen, Dinh Dat; Pham, Van Nhan; Vu, Dinh Lam (Communications in Physics, 2024)
A wideband and high-efficiency bi-functional metasurface for polarization conversion and asymmetric transmission (AT) based on the gratings/ polarization converter/gratings structure is proposed. The proposed metasurface structure consists of a two double-split ring structure array sandwiched by two orthogonal metallic sub-wavelength gratings. Using two orthogonal metallicsub-wavelength gratings, the proposed metasurface reveals excellent AT effect and nearly perfect polarization conversion performance for linearly polarized waves. The proposed metasurface achieves a polarization conversion ratio (PCR) of above 0.99 from 3.7 GHz to 20.2 GHz with a relative bandwidth (RBW) of 138% and an AT parameter of over 0.9 from 5.8 GHz to 17 GHz withan RBW of 99.5%. Moreover, the proposed metamaterial maintains high PCR and AT performance for a wide range of incident angles. Due to its excellent features, such as the wideband and high efficiency of both PCR and AT performances, the proposed bi-functional metasurface can be useful for promising applications such as polarization imaging. radar, radiometer, and transmission.array antennas.